2012
DOI: 10.1371/journal.pone.0040242
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Parathyroid Hormone (PTH) in Patients with Oxidative Stress – Do We Need a Fourth Generation Parathyroid Hormone Assay?

Abstract: Oxidation of PTH at methionine residues results in loss of biological activity. PTH may be oxidized in patients with renal disease. The aim of this study was to develop an assay considering oxidation of PTH. Oxidized hPTH was analyzed by high resolution nano-liquid chromatography coupled to ESI-FTT tandem mass spectrometry (nanoLC-ESI-FT-MS/MS) directly and after proteolytic cleavage. The oxidized hPTH(1–84) sample shows TIC-peaks at 18–20 min and several mass peaks due to mass shifts caused by oxidations. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 26 publications
0
74
0
1
Order By: Relevance
“…Despite the improved performance of these assays in some patient groups [35], some anomalous results were still reported [36][37][38].…”
Section: Third-generation Immunoassaysmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the improved performance of these assays in some patient groups [35], some anomalous results were still reported [36][37][38].…”
Section: Third-generation Immunoassaysmentioning
confidence: 99%
“…Amongst other possible degradation products such as deamidation of asparagine (ASN, N) residues, methionine (MET, M) oxidation is likely to be the most prevalent. In vitro studies using high-resolution MS to identify oxidation products, following exposure of these compounds to peroxides, have demonstrated that the methionine residues at positions 8 and 18 of PTH1-34 and PTH1-84 can become oxidised [38,54]. Methionine 8 oxidises more slowly than methionine 18 [55], and both methionine residues can be singly or doubly oxidised (to sulphoxides and sulphones, respectively).…”
Section: Oxidised Pthmentioning
confidence: 99%
See 3 more Smart Citations